Plexiform neurofibromatosis of vulva - Dogra, Bharat B.; Ahmed, Shamshad; Kandari, Ashwani; Virmani, Rohit (International Journal of Research in Medical Sciences, 2017)
Plexiform Neurofibromatosis of vulva is a rare, benign tumor of genital tract arising from nerve sheath of peripheral nerve. It may present as solitary lesion or as part of Von Recklinghausen’s disease. Genitourinary neurofibroma is rare, however clitoris and labia majus happen to be the most frequent location of neurofibromatosis involving female genital tract. We present a case of plexiform neurofibroma arising from left labia majora in a young patient having features of Von Recklinghausen’s disease. She complained of discomfort while walking due to rubbing of pedunculated mass arising from her labia majora. We carried out the surgical excision of the mass followed by primary repair of labia majora. She has been followed up on out-patient basis for about three months without any recurrence so far.